Anti-vibration analysis of vortex probe based on three-axis acceleration measurement. (December 2017) - Sun, Hongjun; Geng, Fei; Yu, Tao; Liu, Ziqi
Abstract: According to the diversity of the pipeline vibration and unicity of vortex signal in direction, a new idea is proposed to distinguish the vortex signal from the vibration interference by the directional character. This idea is applied to improve the anti-vibration performance of vortex flow-meter by a new probe structure based on three-axis accelerometer. Then model analysis is used to optimize the material, and the harmonic response analysis is applied to optimize the shape of probe tip. Finally, experiment is carried out to compare the anti-vibration performance of the traditional piezoelectric vortex probe and the new design. Experimental results show that new probe can accurately distinguish vortex signal from the vibration interference according to the directional character of signal. And its anti-vibration performance is superior to the traditional piezoelectric vortex probe. Highlights: A method is proposed to distinguish the vortex signal by directional character. This method is applied by an optimized probe based on three-axis accelerometerr. The probe can accurately distinguish the vortex signal from vibration interference.